A critical examination of the introduction of drug detection dogs for policing of illicit drugs in New South Wales, Australia using Kingdon's 'multiple streams' heuristic. (17th November 2017) - Lancaster, Kari; Ritter, Alison; Hughes, Caitlin; Hoppe, Robert
Abstract : This paper critically analyses the introduction of drug detection dogs as a tool for policing of illicit drugs in New South Wales, Australia. Using Kingdon's 'multiple streams' heuristic as a lens for analysis, we identify how the issue of drugs policing became prominent on the policy agenda, and the conditions under which the alternative of drug detection dogs for illicit drugs policing came to be endorsed by decision makers. By applying Kingdon's heuristic, we also consider how this approach may be used to illuminate the limitations of the evidence-based policy paradigm in the context of policing policy.